Museums, U.S.A. : a history and guide / Herbert and Marjorie Katz. - Katz, Herbert M. (Doubleday, 1965)
Provides an entertaining social history and a unique reference guide, because it tells where the museums are as of 1965, how they got there, who put them there, and what they contain. The Appendix includes a listing by state and city of more than 2500 operating museums. The index is cross-referenced, so that it is possible to locate anything from an important Rembrandt to a major entomological collection.